Attentional performance may help to identify duloxetine responders in chronic pain fibromyalgia patients. (1st February 2017) - Schmidt, G.; Alvarenga, R.; Manhães, A.; Schmidt, S.
Abstract: Background: Long‐term pain affects brain in response to attention tasks. This study aimed to verify the relationship between performance in a computerized visual attention test (CVAT) and response to duloxetine in fibromyalgia patients. Duloxetine is approved for the treatment but the response is not immediate. Methods: Patients were drawn from a sample of 74 patients with chronic pain. These patients were selected because they kept their subjective perceptions of pain as severe after 1 week of duloxetine treatment. All patients were tested in the CVAT on two occasions: the first appointment and 7 days after starting duloxetine. Results: After 6 weeks, the group was subdivided into responsive and non‐responsive patients. Responsiveness was defined by a subjective improvement from severe to low‐intensity or no‐pain after the sixth week of duloxetine treatment. Responsive patients showed objective attentional improvements in the second test. Non‐respondent patients did not exhibit changes in attentional performance in the second test as compared to the first one. Conclusions: The data were interpreted considering that persistent pain in fibromyalgia is maintained by central sensitization that may be associated with functional changes in the dorsolateral prefrontal cortex and the posterior parietal cortex. In responsive patients, duloxetine treatment may be responsible for a partial recovery of these regions. This may explain the early attentional improvement observed in the responsive patients after 1 week of treatment. Thus, attentional performance may help to predict which patients will respond to duloxetine treatment even before they can demonstrate subjective improvements in pain perception. Significance: This study shows that an improvement in an attentional test is a reliable predictor of the treatment response even without any improvement in the perception of pain.